(untitled) (Malaysian Management Journal, 2000)
Despite the general notion that distinctive capabilities are crucial to the success affirms, empirical studies that focused on this strategic variable in SMEs remains limited. This study seeks to address this research issue by empirically investigating 100 SMEs in the Malaysian manufacturing sector. The findings of the study suggest that the SMEs studied established capabilities in several business functional areas. In addition, the results of the correlations indicate statistically significant positive relationship between distinctive capabilities and the performance of the SMEs in this study.